Ethnocultural Diversity in Homicide Crime Scene Staging - Dayan, Ḥaṿah (Homicide studies, 2024)
Homicide crime scene staging (HCSS) involves purposefully altering the death scene to obstruct the criminal justice process by concealing the true nature of a crime. It is one of the most perplexing and intriguing homicidal behaviors and one of the least systematically studied, particularly in non-Western societies. As the first systematic study of HCSS in a non-Western society, this paper contributes to the ethnocultural understanding of HCSS by analyzing nation-based data regarding 56 HCSS events in Israel (excluding the West Bank and Gaza) during a 40-year period (1980–2019). Descriptive statistics demonstrate HCSS in Israel differs from that reported by studies in Western societies regarding weapon of choice and the death scene scenario offenders tend to stage. Comparative analysis of the two main ethnic groups in Israel, Jewish and Arab, demonstrates ethnic diversity in HCSS frequency, killing motive, victim characteristics, and victim–offender relations.